Development of shrinkage limit specification for high performance concrete used in bridge decks. (September 2016) - Fu, Tengfei; Deboodt, Tyler; Ideker, Jason H.
Abstract: Early-age cracking of high performance concrete (HPC) structures, in particular bridge decks, results in additional maintenance costs, burden on serviceability, and reduced long-term performance and durability. The causes behind cracking in HPC are well known and documented in the existing literature. However, appropriate shrinkage limits and standard laboratory/field tests are not clearly established in either the technical literature or in specifications. The purpose of this research was to provide shrinkage threshold limits for specifications which allow proper criteria to ensure crack-free or highly cracking-resistant HPC. The restrained ring test (ASTM C1581) was used to identify the cracking potential of 14 different HPC mixtures. By comparing free shrinkage (ASTM C157, 75 × 75 × 285 mm specimen) and restrained shrinkage tests results, a free shrinkage limit of 450 microstrain at 28 days was proposed to ensure satisfactory cracking resistance.